Ploidy plasticity drives fungal resistance to azoles used in agriculture and clinics. - Kaustuv Sanyal; Aswathy Narayanan (PLoS Biology)
The rapid growth in antimicrobial resistance is of great medical concern. A new study in PLOS Biology unveils the link between ploidy plasticity and the emergence of antifungal resistance in Candida tropicalis.